A genome-wide association study of anorexia nervosa suggests a risk locus implicated in dysregulated leptin signaling - Li, Dong; Chang, Xiao; Connolly, John J.; Tian, Lifeng; Liu, Yichuan; Bhoj, Elizabeth J.; Robinson, Nora; Abrams, Debra; Li, Yun R.; Bradfield, Jonathan P.; Kim, Cecilia E.; Li, Jin; et al. (Scientific reports, 2017)
We conducted a genome-wide association study (GWAS) of anorexia nervosa (AN) using a stringently defined phenotype. Analysis of phenotypic variability led to the identification of a specific genetic risk factor that approached genome-wide significance (rs929626 in EBF1 (Early B-Cell Factor 1); P = 2.04 × 10 −7 ; OR = 0.7; 95% confidence interval (CI) = 0.61–0.8) with independent replication ( P = 0.04), suggesting a variant-mediated dysregulation of leptin signaling may play a role in AN. Multiple SNPs in LD with the variant support the nominal association. This demonstrates that although the clinical and etiologic heterogeneity of AN is universally recognized, further careful sub-typing of cases may provide more precise genomic signals. In this study, through a refinement of the phenotype spectrum of AN, we present a replicable GWAS signal that is nominally associated with AN, highlighting a potentially important candidate locus for further investigation.